CASE REPORTSFish tank granuloma – sporotrichoid form as a result of a bite by a tropical fish - Kijowski, Robert; Wróblewska, Joanna; Kaszuba, Aleksandra (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2008)
Fish tank granuloma (swimming pool granuloma) is an infection caused by an atypical Mycobacterium named Mycobacterium marinum (M. marinum), which gets into the organism across the abraded skin mainly in the conditions of occupational or recreational exposure to the contaminated water in closed tanks. Granulomatous changes which occur as the result of a bite of a fish fancier by a tropical fish, as in our case, are rarer. Also, sporotrichoid form of infection by M. marinum is not common (it was not observed previously in Polish literature). It occurs in about 20% of cases and it can cause a big diagnostic problem especially in the initial phase of infection and without precise medical history. The work presents diagnostic possibilities of fish tank granuloma and the result of associated treatment.